Forest operations for sustainable forestry in the tropics: proceedings of a symposium organised by IUFRO Subject group S3.05-00, Forest operations in the tropics at the XX IUFRO World Congress, 6 - 12 August 1995, Tampere, Finland. - Dykstra, D.P. (IUFRO and CIFOR, 1996)
Forest harvesting and transportation operations are essential components of sustainable forestry. Recognition of these important factors was consistent with the theme of the XX IUFRO World Congress, "Caring for the Forest: Research in a Changing World". The Congress was held in Tampere, Finland, in August 1995. As part of the proceedings a forum was provided for discussion of new techniques for planning, implementing and controlling forest operations in ways that promote sustainable management of tropical forests. This volume is the Proceedings of the Symposium organised by IUFRO Subject Group S3.05-00, "Forest Operations in the Tropics". A range of technologies is discussed across a number of regions. A paper by Migunga discusses forest soil compaction in Tanzania, while Cordero and Howard evaluate the use of oxen for logging operations in Costa Rica. Rubini Atmawidjaja addresses the management of ecosystems in Indonesia to balance human and environmental needs. Elias studies forest harvesting damages in East Kalimantan while Aulerich reviews the application of skyline systems by one Indonesian company. Shi Mingzhang presents the forest management accomplishments of the Leizhou Forestry Bureau in Quandong province, southern China. A Mexican case study of damage evaluation in a timber yarding operation is presented by Hernández-Diáz and Delgado-Pacheco while the situation for forest operations in the Amazon Basin is reviewed by Malinovski. Cedergren et al. assess the impacts of selective logging on silvicultural values in a mixed dipterocarp forest of Sabah.